Evaluation of the Performance of GNSS Antennas and Modules for Electronic Navigation Seals under Challenging Operating Conditions - Aitmagambetov, Altay; Zhumagali, Sabyrzhan; Kulakayeva, Aigul; Sultanbekova, Leila; Samsonenko, Anatoly (Engineering, Technology & Applied Science Research, 2026)
This study focuses on the experimental selection of the optimal Global Navigation Satellite System (GNSS) antenna for integration into a domestically developed navigation seal designed for transport logistics and digital customs control tasks in the Republic of Kazakhstan. The relevance of this study stems from the need to enhance technological independence and improve cargo monitoring efficiency to support domestic manufacturing and technological self-reliance. The scientific novelty lies in a comprehensive comparative assessment of commercial antennas not only in laboratory settings but also under field conditions, including installation on metallic surfaces, which reflects real operational scenarios. The objective of the research is to select an antenna that ensures the best balance between cost and performance for integration into the locally developed navigation seal. To achieve this, laboratory measurements and field experiments were conducted, analyzing parameters such as cold start time, carrier-to-noise density ratio (C/N₀, dB-Hz) for each satellite, the number of visible and used satellites, accuracy indicators (Position Dilution of Precision (PDOP), Horizontal Dilution of Precision (HDOP), Vertical Dilution of Precision (VDOP)), and tracking stability under internal and external shielding effects. As a result, the 1575R-A antenna was identified as having the most favorable characteristics among the tested samples and can be recommended for integration into the developed navigation seal. The practical significance of the study lies in providing recommendations for local manufacturers, whereas its theoretical contribution is the expansion of knowledge on the impact of structural and operational factors on the efficiency of GNSS antennas in compact devices.